The impact of dietary salt on the development of hypertension and gut microbiome dysbiosis in captive-bred vervet monkeys (Chlorocebus aethiops) - Zandisiwe Emilia Magwebu; Sanele Khoza; Mikateko Mazinu; Esme Jordaan; Meenu Ghai; Chesa Gift Chauke (BMC Veterinary Research)
Abstract Background The study was designed to establish a hypertensive nonhuman primate model to evaluate the role of dietary salt intake on blood pressure levels and gut microbiome regulation. Sixteen adult vervet monkeys were selected and assigned into two groups (control and experimental). The control group was given a maintenance diet (100 g), whereas the diet of the experimental group was supplemented with 1.5 g/day of dietary salt in the mornings for six months (T0-T6), thereafter, the dose was increased to 2 g/day for additional six months (T9-T12). Blood and stool samples were collected for biochemical and 16 S ribosomal RNA gene sequencing. Results The control group was borderline hypertensive (134.7/62.9 mmHg), whereas elevated blood pressure levels (171.3/81.3 mmHg) were observed at T12 indicating the experimental group to be salt sensitive. Furthermore, gut microbiome analysis showed two main phyla, Bacteroidetes and Firmicutes. However, there was no significant difference for alpha and beta diversity for both groups. Conclusion These findings suggested that dietary salt intake (1.5–2 g/day) caused alterations in systolic blood pressure levels, chloride and alkaline phosphatase (ALP). However, these changes were not associated with gut microbiome dysbiosis even though significant changes were observed over time for the individual groups.